Community health centers cost savings: Ambulatory care patients in North Carolina. Issue 2 (1st March 2014) - Richard, Patrick; West, Kristina D.; Shin, Peter; Younis, Mustafa Z.; Rosenbaum, Sara
Abstract : In 2010 the Patient Protection and Affordable Care Act boosted the expansion of community health centers (CHCs) with 11 billion in mandatory funding from 2011 to 2015. This study used data from the Medical Expenditure Panel Survey (MEPS) and the North Carolina Behavioral Risk Factor Surveillance System (BRFSS) to assess the cost savings associated with the use of community health centers compared to other primary care providers. After controlling for various demographic, socioeconomic characteristics and health conditions, we found savings at an average of 3, 437 in total expenditures and 1, 211 in ambulatory care expenditures. These results suggest that continuing investment in health centers are important during times of budget cuts in order to improve access to care and to generate cost savings to the healthcare system.